Preparation of Cu Nanocomposites from EDA, DETA, and Jeffamine Cored PAMAM Dendrimers with TRIS and Carboxyl Surface Functional Groups - Erturk, Ali Serol; Gurbuz, Mustafa Ulvi; Tulu, Metin; Bozdogan, Abdurrezzak Emin (SLOVENSKO KEMIJSKO DRUSTVO, 2016)
This study presents the synthesis and UV-Vis characterization of Cu nanocomposites from ethylenediamine (EDA) (E), diethylenetriamine (DETA) (D), and Jeffamine (R) T-403 (P) cored PAMAM dendrimers (PAMAMs) with TRIS and carboxyl surface functional groups. Cu-PAMAM dendrimer encapsulated nanoparticles (Cu-DENs) were characterized by UV-Vis spectroscopy. Disappearance of the 680 nm d-d transition and 270-300 nm ligand to metal charge transfer (LMCT) peaks and the formation of monotically increasing exponential band were used as the evidence of the successful synthesis of Cu-DENs in addition to immediate color change of dendrimer-metal mixture solutions from blue to golden brown by reduction. Synthesized Cu-DENs could be facilitated as novel alternatives to the existing nanomaterials used in a wide range of applications involving bio and chemical sensors, catalysis, hydrogenations, oxidations, semiconductors, noble metals, magnetic dendrimer nanocomposites, environmental cleanup and many others.
Keywords: TRIS and carboxyl terminated PAMAM dendrimers; Dendrimer encapsulated nanoparticles; EDA; DETA; Jeffamine; Cu nanocomposites; MICROWAVE-ASSISTED SYNTHESIS; NANOPARTICLES; GOLD; COMPLEXES; CLUSTERS; CU(II); Chemistry